Establishment and Partial Characterization of Canine Mammary Tumor Cell Lines - Eliza Vazquez; Luis Dominguez; Brian Silverio; Geobanni Torres; Adriana Garibay-Escobar; Felisbina Luisa Queiroga; Carlos Velazquez (Animals)
Mammary tumors are the most common neoplasms diagnosed in female dogs and have been considered excellent models for studying human breast cancer. Establishing cell lines from primary cultures of canine mammary tumors provides an in vitro model to better understand the disease and develop new treatments. This study aimed to establish and characterize canine mammary tumor cell lines. Ten cell cultures were generated from tumor tissue obtained from affected dogs, including seven from primary mammary tumors and three from metastatic sites. Characterization included molecular marker expression (ER, PR, HER2, cytokeratin 5/6 (CK5/6), vimentin, and the marker of cell proliferation Ki67) and in vitro tumorigenic capacity assessment. Additionally, the susceptibility of five cell lines to DOX, 5-FU, paclitaxel, colchicine, and carboplatin was evaluated using the MTT assay. ICC analysis revealed negative expression of hormonal receptors (ER and PR) in five cell lines, while only one cell line was positive for both. Six cell lines were HER2-negative and positive for vimentin. Five cell lines exhibited in vitro tumorigenic capacity, forming colonies in soft agar. DOX showed the highest growth-inhibitory effect (DOX > Paclitaxel > Colchicine > 5-FU > Carboplatin). Two cell lines had a minimal concentration for 50% inhibition in vitro (IC50) < 0.63 µM and 4.37 ± 0.40 µM for DOX, while one was sensitive to colchicine and paclitaxel (IC50 0.19 µM and 0.04 µM, respectively). All tested cell lines were resistant to carboplatin and 5-FU. These cell lines provide a valuable model for studying breast cancer in humans and dogs and evaluating new potential therapeutic strategies.